2019
DOI: 10.1245/s10434-019-07844-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Delays in the Treatment of DCIS and the Associated Incidence of Invasive Breast Cancer

Abstract: Background. Although treatment delays have been associated with survival impairment for invasive breast cancer, this has not been thoroughly investigated for ductal carcinoma in situ (DCIS). With trials underway to assess whether DCIS can remain unresected, this study was performed to determine whether longer times to surgery are associated with survival impairment or increased invasion. Methods. A population-based study of prospectively collected national data derived from women with a clinical diagnosis of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 34 publications
0
45
0
3
Order By: Relevance
“…The need to minimize use of operating room resources requires selectively deferring surgery and triaging patients for use of an initial alternative therapy whenever possible. However, level II evidence demonstrates that preoperative delays may impact BC outcomes [5,6].…”
Section: Breast Focused Imagingmentioning
confidence: 99%
“…The need to minimize use of operating room resources requires selectively deferring surgery and triaging patients for use of an initial alternative therapy whenever possible. However, level II evidence demonstrates that preoperative delays may impact BC outcomes [5,6].…”
Section: Breast Focused Imagingmentioning
confidence: 99%
“…The anxiety of nonoperative management of DCIS stems from known sampling error on core biopsy with pathologic upstaging rates ranging from 10% to 30% at the time of operation. 2,12 Although nonoperative treatment of non-high-grade DCIS is being explored in randomized clinical trials in Europe and the US (eg LORD [Low Risk DCIS], 13 LORIS [Low Risk DCIS], 14 and COMET [Comparison of Operative to Monitoring and Endocrine Therapy for Low-Risk DCIS] trials), 15 these trials are enrolling highly selected patients and have yet to report their results. In addition, retrospective data have shown that in patients meeting LORIS criteria, upstage rates at the time of operation might be 7% to 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Time to operation has been shown to be associated with increase in upstaging from DCIS to invasive disease on the order of 1% per month, but with excellent survival rates even in upstaged patients. 2 In invasive cancer patients, studies using nodal positivity as a surrogate outcomes measure have demonstrated mixed results. 3,4 In addition, survival analyses have similarly reported varied findings, leaving surgeons without a clear sense of the repercussions that can result from treatment delays.…”
mentioning
confidence: 99%
“…The management of ductal carcinoma in situ (DCIS) with cryoablation is in keeping with the overall trend to managing DCIS non-operatively, such as with endocrine therapy or surveillance alone in selected patients [10]. However, a recent analysis of the impact on pre-operative delays in patients with DCIS revealed a statistically significant (7.4%) increased relative risk of death for every 30-day interval increase, which shows the potential hazard of simply postponing the management of DCIS until after the pandemic (Priority C) [11]. Indirect evidence supporting the efficacy of cryoablation in the management of DCIS may be derived from studies revealing no residual invasive cancer or DCIS in tissue samples obtained from needle biopsies of cryoablated tumors.…”
Section: Stage 0 Ductal Carcinoma In Situmentioning
confidence: 96%